Thermophysical characteristics of frozen semifinished products for restaurant technology - Koretska, Iryna; Polovyk, Volodymyr; Maslikov, Maxim; Kuzmin, Oleg (My University, 2020)
The aim of the study is to determine the influence of the rmophysical characteristics of frozen semi-finished products on the quality of desserts.
Keywords: cryoscopic; freezing; fruit; dessert; blend; кріоскопія; заморожування; фрукти; кафедра технології ресторанної і аюрведичної продукції; кафедра теплоенергетики та холодильної техніки